Pengelolaan Sistem Informasi Persuratan Elektronik Dalam Mendukung Efektivitas Administrasi Pemerintahan Daerah Pada Dinas Komunikasi dan Informatika Kota Kendari - Sarinah (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Correspondence management is a crucial component of local government administration as it serves as the primary medium for formal communication among regional government organizations. Advances in information technology have encouraged local governments to adopt electronic correspondence information systems in order to enhance bureaucratic efficiency, effectiveness, and accountability. This study aims to analyze the management of an electronic correspondence information system at the Office of Communication and Informatics of Kendari City by examining five main stages, namely the receipt, sorting, recording, follow-up, and storage of correspondence. This research employs a qualitative approach, with data collected through observation, in-depth interviews, and documentation studies. The findings indicate that the processes of receiving and sorting correspondence have been conducted electronically and centrally by correspondence administration officers. However, the recording of correspondence is still carried out manually using agenda books, which has not fully supported the optimization of the electronic correspondence system. Follow-up actions depend on leadership disposition through the digital system, while archiving is implemented through a combination of digital and physical storage as a form of administrative risk control. These findings demonstrate that the electronic correspondence information system has contributed to accelerating administrative workflows, yet further development is required to achieve full integration within local government administrative governance.